Comprehensive sexuality education, sexual risk behaviors and adolescent pregnancy in Oaxaca State students, Mexico - Sánchez Martínez, Noemí; Espinoza-Rivera, Iliana (Horizonte Sanitario, 2024)
Objective: To examine the relationships among comprehensive sexuality education, sexual risk behaviors and adolescent pregnancy in students at a high school in the state of Oaxaca, Mexico.Materials and methods: A survey was conducted using an electronic form, completed by 326 high school students in Oaxaca in 2023. The questionnaire assessed the participants’ history of receiving comprehensive sexuality education and its contents, sexual risk behaviors, sources of information on sexuality, as well as the history of adolescent pregnancy and abortions. The data collected was then described and analyzed to identify any significant relationships among the variables.Results: Comprehensive sexuality education was received by 43.9% of the participants. The overall prevalence of adolescent pregnancy in the sample was 10.1%, with a higher prevalence of 25% among those who had engaged in sexual intercourse. The average age at which participants started engaging in sexual relationships was 15 years, with a range from 12 to 18 years. More than half of the participants reported that their reasons for initiating sexual relationships were not due to their desires. Furthermore, participants who sought information on sexuality from social networks and peers were three times more likely to have initiated sexual relationships. Only 46.2% of participants reported consistent use of contraceptive methods.Conclusions: The study revealed that the comprehensive sex education provided to the participants lacked completeness in its coverage of topics. However, it was associated with a delay in the initiation of sexual relationships, potentially contributing to the reduction in adolescent pregnancy. Additionally, the study highlighted that obtaining information on sexuality from social networks was linked to the adoption of risky sexual behaviors.